Safety and tolerability of hydroxychloroquine in health care workers and first responders for the prevention of COVID-19: WHIP COVID-19 Study - McKinnon, John E.; Wang, Dee Dee; Zervos, Marcus; Saval, Matt; Marshall-Nightengale, Laurie; Kilgore, Paul; Pabla, Pardeep; Szandzik, Ed; Maksimowicz-McKinnon, Kathleen; O'Neill, William W. (International journal of infectious diseases, 2022)
•Hydroxychloroquine chemoprophylaxis is safe in high-risk populations for COVID-19.•No increased cardiovascular risks were observed with hydroxychloroquine chemoprophylaxis.•Adverse events were similar between placebo and hydroxychloroquine treatment arms. Health care workers (HCW) are among the highest risk groups for acquisition of COVID-19 because of occupational exposures. The WHIP COVID-19 Study aimed to evaluate the safety and efficacy of hydroxychloroquine (HCQ) as chemoprophylaxis for SARS-CoV-2 infection in this population. HCW, first responders, and other occupationally high-risk participants were enrolled in a randomized, placebo-controlled clinical study of HCQ from April to October 2020. The trial compared daily versus weekly HCQ with placebo and with a prospective cohort on HCQ for autoimmune diseases. Participants were followed for 8 weeks. Serology or a positive polymerase chain reaction test was used to determine laboratory confirmed clinical cases. A total of 624 participants were randomized to placebo (n = 200), weekly HCQ (n = 201), daily HCQ (n = 197). For the primary safety end point, 279 (44.7%) participants experienced adverse event (AE) level II or lower (total AEs n = 589), similar rates in all randomized groups (P = .188) with no hospitalizations or interventions required. Only 4 laboratory confirmed COVID-19 cases occurred, with 2 in the placebo arm and one in each HCQ randomized arm. This randomized placebo-controlled trial was able to demonstrate the safety of HCQ outpatient chemoprophylaxis in high-risk groups against COVID-19. Future studies of chemoprophylaxis for SARS-CoV-2 are needed as the epidemic continues worldwide.